Análise dos efeitos do tambor-pulmão-corda na eficiência em um sistema produtivo de engenharia sob encomenda - Telles, Eduardo Santos (Universidade do Vale do Rio dos Sinos, 2019)
Increased productivity and efficiency in industries with Engineered to Order (ETOs) production systems have attracted growing interest from the academic and business, and the application of the Drum-Buffer-Rope (DBR) is considered an alternative to traditional improvement programs to achieve these ends. However, although research on DBR shows benefits, empirical evidence is scarce in the literature, especially in ETO production systems. Therefore, it is relevant to evaluate the effects that the implementation of DBR produces to contribute to the improvement of technical efficiency in an ETO system. This research analyzes the effects of the implementation of DBR in three ETO production lines of an electronic company of the Brazilian aerospace sector. These effects were evaluated longitudinally in a period that includes pre and post TPC results, combined with the Data Envelopment Analysis (DEA), the Wilcoxon test and the Analysis of Variance (ANOVA) in a case study. As a result, it is evident that the effects of DBR on efficiency are positive. It is also observed significant differences in the result of the productive efficiency among the three product lines analyzed. Finally, the research establishes which variables and qualitative aspects contributed, positively or not, to the productive efficiency after the DBR implementation.
Keywords: Teoria das Restrições (TOC); Tambor-Pulmão-Corda (TPC); Eficiência; Engenharia sob Encomenda (ETO); Análise Envoltória de Dados (DEA); Theory of Constraints (TOC); Drum-Buffer-Rope (DBR); Engineering to order (ETO); Data Envelopment Analysis (DEA); ACCNPQ::Engenharias::Engenharia de Produção